2017
DOI: 10.1016/j.jtherbio.2016.11.013
|View full text |Cite
|
Sign up to set email alerts
|

A critical review of the use and performance of different function types for modeling temperature-dependent development of arthropod larvae

Abstract: Temperature-dependent development influences production rates of arthropods, including crustaceans important to fisheries and agricultural pests. Numerous candidate equation types (development functions) exist to describe the effect of temperature on development time, yet most studies use only a single type of equation and there is no consensus as to which, if any model predicts development rates better than the others, nor what the consequences of selecting a potentially incorrect model equation are on predic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 79 publications
2
49
0
Order By: Relevance
“…Thus, efforts were made to develop models reducing the number of parameters (e.g., Briere model; Figure 2C), while keeping key model characteristics: (1) the asymmetry in development rate with a sharp decline above optimal temperature of development, and (2) the characterization of a lower and upper threshold of development (Briere et al, 1999;Shi et al, 2015). Despite these advances and Lamb's evidence on nonlinearity and the development of simplified models (above), to date the straight-line equation is still the most used in papers (Quinn, 2017;Rebaudo et al, 2017), even if it is biased at extreme temperatures.…”
Section: Biophysical Vs Statistical Modelsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, efforts were made to develop models reducing the number of parameters (e.g., Briere model; Figure 2C), while keeping key model characteristics: (1) the asymmetry in development rate with a sharp decline above optimal temperature of development, and (2) the characterization of a lower and upper threshold of development (Briere et al, 1999;Shi et al, 2015). Despite these advances and Lamb's evidence on nonlinearity and the development of simplified models (above), to date the straight-line equation is still the most used in papers (Quinn, 2017;Rebaudo et al, 2017), even if it is biased at extreme temperatures.…”
Section: Biophysical Vs Statistical Modelsmentioning
confidence: 99%
“…The characterization of the relationship between temperature and development rate is still a challenge, notably because of mortality at extreme temperatures and interindividual variation within the same species (R egni ere et al, 2012), which makes model choice constrained by uncertainty. In the review of the various performance functions modeling temperature-dependent development of arthropods, Quinn (2017) revealed that model choice is of critical importance because of the significant differences between model predictions (see also Shi et al, 2015;and Figure 1B-D). In Quinn's (2017) study, although no function type was described as standing out from the rest, considering and comparing various functions in regard to the available datasets should lead to better predictions.…”
Section: Recent Advances and Future Directionsmentioning
confidence: 99%
See 3 more Smart Citations